Corporate Governance: The Importance of Implementing Good Corporate Governance for Business Sustainability and Improving Company Performance and Value - Sitti Zulaeha; Kartini; Hamid Habbe; Syarifuddin Rasyid (IECON: International Economics and Business Conference, 2023)
The implementation of GCG can improve company performance, especially financial performance and reduce risks that may be carried out by the Board of Directors to makedecisions that benefit themselves, and in general Corporate Governance can increase investor confidence. Meanwhile, the low implementation of Corporate Governance canreduce the level of investor confidence and can be a factor that prolongs the economic crisis in Indonesia. Healthy business practice is the implementation of organizational functions based on good management principles (good corporate governance) in the context of providing quality and sustainable services. In the phenomenal growth of corporate governance, social power and organizational influence have both contributed to taking responsibility for balancing their own interests. Corporate governance is related to the ways in which financial suppliers to companies ensure that they get returns on investment (Amanah, Dhiana and Fathoni: 2018). A set of mechanisms by which outside investors protect themselves against takeovers by managers and controlling shareholders. The guideline is the company's mechanism for determining which ones should reduce agency costs and better align the interests of the board and capital suppliers (Dimopoulos and Wagner: 2016). Corporategovernance as the system of laws, rules, and factors that control the operations of an organization. These norms and laws have shaped the relationship between the board ofdirectors, shareholders and managers as well as to resolve agency conflicts (Kalemli- Ozcan and Fan: 2016).